Viscoelastic model for analysing the behaviour of adhesive-bonded FRP-to-steel joints in civil engineering applications. (April 2023) - Wang, Songbo; Stratford, Tim; Reynolds, Thomas
Abstract: Adhesively bonding fibre reinforced polymer (FRP) plates have been a mainstream method for strengthening civil engineering structures. The effectiveness of bonding strengthening is dependent on the performance of the adhesive layer. This study examines the time-temperature dependent viscoelasticity of a typical structural epoxy adhesive and develops a linear viscoelastic material model that can be used for numerical analysis. An accelerated test method involving dynamic mechanical analysis (DMA) and time-temperature superposition principle (TTSP) were used to characterise the structural adhesive. The corresponding limitations of this method were discussed, including decomposition effect, nonlinear viscoelasticity, applicability of TTSP, and further curing of the sample. The numerical study of the long-term behaviour of the single lap-shear FRP-to-steel joint found that a slightly warmer temperature (30 °C for this study) is beneficial for the bonded joint as it can reduce the concentrated shear stress with negligible increase in the shear strain. However, a higher temperature (50 °C for this study) that near the adhesive's glass transition temperature ( T g ) could be detrimental as it can lead to significant shear strain in the adhesive joint within the first year of service life.